Postantibiotic, Postantibiotic Sub-MIC, and Subinhibitory Effects of PGE-9509924, Ciprofloxacin, and Levofloxacin - Odenholt, Inga (American Society for Microbiology, 2003)
Postantibiotic effects (PAEs), postantibiotic sub-MIC effects, and sub-MIC effects of the new nonfluoroquinolone PGE-9509924, ciprofloxacin, and levofloxacin against gram-positive and gram-negative strains were investigated. In comparison to ciprofloxacin and levofloxacin, PGE-9509924 exerted very similar PAEs against all strains except for both strains of Streptococcus pneumoniae, where longer PAEs were found for PGE-9509924. All three investigated quinolones showed no minimal PAEs against Pseudomonas aeruginosa.